Hydrogen generation by photocatalytic reforming of potential biofuels: Polyols, cyclic alcohols, and saccharides - Julia Kennedy (2018)
© 2018 Elsevier B.V. We have studied hydrogen gas production using photocatalysis from C2-C5 carbon chain polyols, cyclic alcohols and mono and di-saccharides using palladium nanoparticles supported on a TiO2catalyst. For many of the polyols the hydrogen evolution rate is found to be dictated by the number of hydroxyl groups and available α-hydrogens in the structure. However the rule only applies to polyols and cyclic alcohols, while the sugar activity is limited by the bulky structure of those molecules. There was also evidence of ring opening in photocatalytic reforming of cyclic alcohols that involved dehydrogenation and decarbonylation of α C–C bond.